2019
DOI: 10.1787/059ce467-en
|View full text |Cite
|
Sign up to set email alerts
|

Strength through diversity’s Spotlight Report for Sweden

Abstract: OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed herein are those of the author(s). Working Papers describe preliminary results or research in progress by the author(s) and are published to stimulate discussion on a broad range of issues on which the OECD works. Comments on Working Papers are welcome, and may be sent to the Directorate for Education and Skills, OECD,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
(77 reference statements)
0
7
0
2
Order By: Relevance
“…Language can be an important barrier to the inclusion in education of some diverse student groups, mainly for those from an immigrant background and some Indigenous communities. Language is an essential component of educational policy to guarantee not only improved educational outcomes, but also the wellbeing, sense of belonging and self-worth of these student groups (OECD, 2017 [4]; Cerna, 2019 [5]). During school closures, some countries have included a language component in their policy response in order to foster the inclusion of these vulnerable groups.…”
Section: Distributing Information and Providing Online Resources In D...mentioning
confidence: 99%
“…Language can be an important barrier to the inclusion in education of some diverse student groups, mainly for those from an immigrant background and some Indigenous communities. Language is an essential component of educational policy to guarantee not only improved educational outcomes, but also the wellbeing, sense of belonging and self-worth of these student groups (OECD, 2017 [4]; Cerna, 2019 [5]). During school closures, some countries have included a language component in their policy response in order to foster the inclusion of these vulnerable groups.…”
Section: Distributing Information and Providing Online Resources In D...mentioning
confidence: 99%
“…There is a large body of empirical literature that analyses the extent to which local authorities allocate targeted grants according to the intentions or recommendations of the funding authority. While early findings in the area reported that additional grants were to a large extent spent as intended, recent empirical studies identify mixed effects on local authorities' spending (Brunner, Hyman and Ju, 2020 [48]; Cascio, Gordon and Reber, 2013 [49]; Hyman, 2017 [50]). These studies suggest that this effect may be sensitive to the design and target of the grant, as well as to economic circumstances and institutional settings.…”
Section: Box 2 Norway's Experience With the Limitations Of Additional...mentioning
confidence: 99%
“…The first phase of the project developed a comprehensive set of reports (OECD, 2018 [7]; OECD, 2018 [30]; OECD, 2019 [31]) and working papers (Cerna et al, 2019[32]; Guthrie et al, 2019[33]; Borgonovi and Pokropek, 2017 [34]; 2018 [35]; Cerna, 2019 [36]; Forghani-Arani, Cerna and Bannon, 2019 [37]; Bilgili, 2017 [38]; 2019 [39]) examining migration-induced diversity and the effects it has on education systems. Following the framework developed in the first phase of the project, the second phase considers broad migration experiences individuals may have, whether direct (foreign-born individuals who migrated) or not (individuals who have at least a parent or guardian who migrated).…”
Section: Migration-induced Diversitymentioning
confidence: 99%